Sublingual Sufentanil vs. Intravenous Fentanyl for the Treatment of Acute Postoperative Pain in the Ambulatory Surgery Center: A Randomized Clinical Trial. (8th July 2022) - Berg, Aaron; Habeck, Jason; Strigenz, Michael; Pearson, Jonah; Kaizer, Alexander; Hutchins, Jacob
Abstract : Objectives . Sublingual sufentanil is a novel opioid medication to treat moderate to severe pain postoperatively. This study's aim was to determine if a single dose of a sublingual sufentanil tablet (SST) is as efficacious as a single dose of intravenous (IV) fentanyl in readiness to discharge from ambulatory surgery. Methods . This was a two-arm, parallel group, randomized prospective outcomes study conducted at a single, free-standing ambulatory surgery center. Patients aged 18–80 undergoing general anesthesia who developed a postoperative pain score of ≥ 4 were enrolled and randomized to receive either 30 mcg SST or 50 mcg IV fentanyl. After their initial randomized dose, rescue IV fentanyl followed by oral oxycodone if needed. Recovery length of stay from arrival in the postanesthesia care unit until readiness to discharge criteria was met based on phase 2 discharge criteria. Results . 75 patients were analyzed. Readiness to discharge from the recovery room was not significantly different between either group (IV fentanyl median 65 minutes; IQR 56–89; SST 73 min, IQR 58–89; p = 0.903 ). There was no significant difference in the amount of morphine equivalents (MME) of rescue opioids needed (IV fentanyl median rescue MME of 22.5, IQR 13.1–23.4; SST median rescue MME of 15.0, IQR 7.5–30.0; p = 0.742 ). The change in pain from PACU initially, and on discharge was not significantly different (IV fentanyl initial pain minus pain on discharge median 3, IQR 2–4; SST initial pain minus pain on discharge median 4, IQR 2–5.5; p = 0.079 ). There was no difference in the six-item screener and the Overall Benefit of Analgesic Survey Score. Discussion . In conclusion, patients who received a sublingual sufentanil 30 mcg tablet had no significant differences in PACU length of stay or rescue analgesic usage when compared to intravenous fentanyl 50 mcg.